Patient perceptions and preferences of minimally invasive treatment modalities in varicose veins: a cross-sectional survey - Li, Qian; Wang, Xiaotao; Meng, Bin; Chen, Xinle; Xu, Mingmin (Frontiers in Cardiovascular Medicine, 2024)
Purpose Minimally invasive therapies (MIT) have gained popularity due to their capacity to reduce trauma, enhance aesthetic outcomes, and shorten recovery periods. This article explores patients’ perceptions and preferences regarding MIT for varicose veins (VVs) while analyzing associated influencing factors to provide a better understanding. Patients and methods A cross-sectional survey at Zhejiang Rongjun Hospital was performed from January 2022 to June 2023, involving 305 participants with VVs. The questionnaire assessed patient demographics, VVs severity, prior treatment experiences, and treatment preferences. Statistical analyses, including chi-square and Kruskal-Wallis tests, were conducted to explore the correlations between patient characteristics, treatment preferences, and factors influencing these choices. Results Nearly half of the participants (44.3%) lacked information on any surgical options, whereas a slight majority (55.7%) possessed familiarity with at least one treatment modality, and only 9.8% knew of all six treatment methods presented. Patient surveys discerned that the majority (68.5%) declared an inadequate grasp of treatment methodologies to articulate a treatment preference. Among the 96 patients who made a treatment choice, 24.0% opted for traditional surgery, while 76.0% chose MIT and a higher preference for MIT among male patients compared to female patients (p = 0.006). The patients preferred treatment options for VVs significantly affected by vascular surgeon recommendations and the number of follow-up visits (r = 0.129, p = 0.024; r = 0.122, p = 0.033). Conclusion The study highlights limited awareness of MIT among Chinese patients with VVs. The insights emphasize the influential role of vascular surgeons’ recommendations and suggest a growing predilection for less invasive treatments due to their advantages in recovery and aesthetics. Provider-patient communication, including education about available treatments and shared decision-making, is essential to align treatment plans with patient expectations and improve outcomes.